A Study on Entrepreneurship Education in Western Countries: Retrospectives on Entrepreneurship Curricula and Instructions - Nisa Novia Avien Christy; Ming Chang Wu (International Journal of Research in Education (IJRE), 2022)
Unemployment is now a major problem that must be resolved immediately. The unemployment rate in Indonesia is higher than in western countries. This is because the number of entrepreneurs in Indonesia is still deficient. This study is conducted to synthetically analyze the empirical experiences of enhancing entrepreneurship in Western countries. This further understanding will be transformed and applied to Indonesian universities and societies. This study uses literature analysis approaches to find references to relevant theory with the hope that researchers can in-depth understand the experiences and the significant factors facilitating entrepreneurship in Western countries. At the end of the study, the authors conclude that the success of entrepreneurship in western countries is due to central government support for entrepreneurship. Therefore, the success of entrepreneurship in western countries that can be applied in Indonesia, such as (1) the Indonesian government must endeavor to oblige all universities in Indonesia to provide entrepreneurship classes, (2) promote entrepreneurship education and make entrepreneurship a priority, (3) implementing entrepreneurship in educational curricula at all levels, starting with preschool. , (4) providing educational scholarship facilities for economic and business actors to become entrepreneurs, (5) providing (people's business credit) with low interest for business.